STRATEGI PEMASARAN PRODUK PAKAIAN DENGAN SISTEM ONLINE DAN OFFLINE PADA TOKO KANAYA COLLECTION DI KOTA NEGERI LAMA LABUHAN BATU SUMATERA UTARA - Lestari, Ayu; Maisyura, Maisyura (Program Studi Administrasi Bisnis, 2023)
Online and Offline Marketing Strategy is marketing carried out through an interactive online computer system, which connects consumers with sellers via the internet network, the internet is a term used to describe interacting with each other through social media accounts in the form of Facebook, making it possible to communicate. The research results show that: Online and Offline Marketing Strategy by collaborating and being able to increase sales at the Kanaya Collection Shop, Online Marketing Strategy by promoting products through social media accounts in the form of Facebook and can be maximized because it is able to bring in more consumers. and Offline Marketing Strategy, there is an increase in sales because consumers who come to the Kanaya Collection Shop can see directly the varied products and also affordable prices and strategic locations so that consumers are interested in shopping at the Kanaya Collection Shop.